The framing of the coverage of the Gaza withdrawal by Israeli forces in the Cape Times, Mail & Guardian and Sunday Times from July 1, 2005 to September 12, 2005 - Silke, Bryan David (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2007.